2008
DOI: 10.1021/jm800889m
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Eszopiclone and Zolpidem Binding to the γ-Aminobutyric Acid Type-A (GABAA) Receptor Are Different

Abstract: The sleep-aids, zolpidem and eszopiclone, exert their effects by binding to and modulating GABAA receptors (GABAARs), but little is known about the structural requirements for their actions. We made 24 cysteine mutations in the benzodiazepine (BZD) binding site of α1β2γ2 GABAARs, and measured zolpidem, eszopiclone, and BZD-site antagonist binding. Mutations in γ2Loop D and α1Loops A and B altered the affinity of all ligands tested, indicating that these loops are important for BZD pocket structural integrity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(104 citation statements)
references
References 47 publications
7
89
0
8
Order By: Relevance
“…The present study focuses on the orientation of classic BZDs in the binding pocket, and it is unclear whether non-BZD ligands orient similarly; however, mutagenesis and docking studies of the non-BZD ligands zolpidem and eszopiclone indicate that interactions with ␣ 1 His101, ␣ 1 Ser204, and ␥ 2 Arg194 contribute to orienting these ligands in the binding pocket (Hanson et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…The present study focuses on the orientation of classic BZDs in the binding pocket, and it is unclear whether non-BZD ligands orient similarly; however, mutagenesis and docking studies of the non-BZD ligands zolpidem and eszopiclone indicate that interactions with ␣ 1 His101, ␣ 1 Ser204, and ␥ 2 Arg194 contribute to orienting these ligands in the binding pocket (Hanson et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Mutation of the homologous W55 residue in the GABA A -R ␥2-subunit, F77C, abolished binding by (28). In the GABA A -R ␣1-subunit, it was shown that for the homologous Trp-55 subtle changes were caused by unnatural amino acid mutations (29).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the predominant heteromeric receptors where the binding interfaces will differ, such ligands may possibly serve as positive or negative allosteric modulators at sites distinct from those occupied by agonist and competitive antagonist (36). Such appears to be the case for the benzodiazepines (36,37) and other sedative agents (38) that act in this manner with the GABA receptor (39,40). Accordingly, new dimensions for achieving pharmacologic selectivity for particular nAChR subtypes may result with the cooperative nAChR ligands possessing electron-rich substituted 2-aminopyrimidines.…”
Section: Discussionmentioning
confidence: 99%